Post-annealing effect on transparent Mg-Zn aluminate solid solutions fabricated by spark plasma sintering. Issue 16 (December 2019) - Nam, Sangwoo; Kang, Shinhoo; Kim, Byung-Nam; Jung, In-Ho; Kim, Young-Min
Abstract: In MgAl2 O4 (Mg aluminate) fabricated by pressure sintering, carbon contamination, oxygen vacancy, and other defects exist and cannot be completely removed even after post-annealing. ZnAl2 O4 (Zn aluminate) has the same crystallographic structure as Mg aluminate and excellent light transmission by post-annealing. In this study, the transmission of (Mg1-X ZnX )Al2 O4 spinel, which is a solid solution between Mg aluminate and Zn aluminate, was investigated. After post-annealing, the transmission of (Mg1-X ZnX )Al2 O4 spinel was higher than Zn aluminate and Mg aluminate, which means that the absorption center disappeared. Besides, the real in-line transmission is improved by up to 30% by post-annealing, which is related to the driving force to increase the configurational entropy and form a more stable solid solution phase. In solid solution spinel, as the Zn content increases, the optical properties can be improved by post-annealing, but the mechanical properties are slightly decreased.